2017
DOI: 10.14720/aas.2017.109.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Bivariate analysis of the genetic variability among some accessions of African Yam Bean (Sphenostylis stenocarpa (Hochst ex A. Rich)Harms)

Abstract: Variability is an important factor to consider in crop improvement programmes. This study was conducted in two years to assess genetic variability and determine relationship between seed yield, its components and tuber production characters among twelve accessions of African yam bean. Data collected were subjected to combined analysis of variance (ANOVA), Principal Component Analysis (PCA), hierarchical and K-means clustering analyses. Results obtained revealed that genotype by year (G × Y) interaction had sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…However, each coefficient of proper vectors indicates the degree of contribution of every original variable with which each principal component is associated. The higher the correlation coefficient (positive or negative), the more effective in discriminating varieties [38,39]. In the current study, the results of PCA showed that PC1-8 was responsible for 75.13% of the total variation, and PC1-4 explained 50.39% of the total variation, accounting for most of the variability observed among the rice genotypes from different locations.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…However, each coefficient of proper vectors indicates the degree of contribution of every original variable with which each principal component is associated. The higher the correlation coefficient (positive or negative), the more effective in discriminating varieties [38,39]. In the current study, the results of PCA showed that PC1-8 was responsible for 75.13% of the total variation, and PC1-4 explained 50.39% of the total variation, accounting for most of the variability observed among the rice genotypes from different locations.…”
Section: Discussionsupporting
confidence: 48%
“…The dendrogram of 43 genotypes, their two parents, and three checks resulted in five clustered groups and one of the parents as an outgroup (TOG 5681) to the clusters at a similarity index of 0.49. The first cluster comprised of two intraspecific genotypes (1,3), the second cluster encompasses a majority of the genotypes distributed into four subclusters which include cluster IIA comprising of three intraspecific genotypes (2,4,7), cluster IIB comprised of six genotypes that are both intraspecific and interspecific (5,6,15,16,17,19), likewise cluster IIC comprised of twenty genotypes (8,9,10,11,18,24,28,36,40,35,37,38,39,27,23,45,30,33,34,12) while are all interspecific genotypes except genotype 45 which represents one of the parents, IR64,while the last subcluster, IID, comprised of three genotypes (20,29,42) that are interspecific in nature. The third cluster is composed of four interspecific genotypes (13,14,25,26).…”
Section: Clustering Of Rice Genotypesmentioning
confidence: 99%
“…However, tuber yield showed negative and non-significant association with seed yield indicating that both seed yield and tuber yield are not complementing each other. Similarly Akinyosoye et al, (2017) also reported that non-significant relationship existed between tuber and seed yield per plant. Tuber yield recorded negative association with pods per plant, pods per peduncle, number of seeds per pod and seed yield indicating that varieties should be developed in desired direction by considering these traits.…”
Section: Resultsmentioning
confidence: 96%
“…Except for Africa, no other continent has a record of the crop's origin (Adewale et al, 2008). Although not all African yam bean (AYB) produce tubers, it is considered a dual crop because it has both tubers and seeds (Akinyosoye et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One of the major constraints affecting the utilization and adoption of AYB is late maturity, low seed yield, and extra agronomic practices like staking (Popoola et al, 2019). The majority of known accessions of AYB are late maturing, with physiological maturity occurring between 6 and 7 months following sowing, depending on genotypes (Akinyosoye et al, 2017). Mutation breeding is a fast, costeffective, reliable, and proven strategy for creating and selecting novel agronomic characters (FAO/IAEA, 2017), which aids in the identification and release of novel genes that govern the traits of interest (FAO/IAEA, 2017).…”
Section: Introductionmentioning
confidence: 99%